NILAI EKONOMI HASIL HUTAN BUKAN KAYU DALAM MENDUKUNG LIVELIHOOD BERKELANJUTAN : STUDI KASUS DI DESA HARUKU - Sofia Mustamu; Victor Leo Nolly Kewilaa (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
Non-Timber Forest Products (NTFPs) play a vital role in supporting the livelihoods of rural communities, particularly those living in or around forested areas. This study aims to assess the economic value of NTFPs and their contribution to sustainable livelihoods in Haruku Village, Central Maluku Regency. Utilizing a mixed-methods approach that combines household surveys, key informant interviews, and direct observation, the research evaluates the income derived from various types of NTFPs and examines their role in the economic resilience and sustainability of local households. The results show that income generated from NTFPs reached IDR 1,393,010,000, while income from non-NTFP sources amounted to IDR 1,256,808,450, resulting in a total household income of IDR 2,649,818,450. The contribution of NTFPs to the total income of Haruku Village households is categorized as moderate, accounting for 52.57%. Among the various NTFPs, three main products were found to contribute significantly to household income: cloves (47.02%), sago (17.69%), and durian (10.97%). This study highlights the importance of integrating NTFPs into local and regional development strategies to enhance economic sustainability and ecological balance in forest-dependent communities.